Sunitinib for Metastatic Renal Cell Carcinoma: Real-World Data from the STAR-TOR Registry and Detailed Literature Review - Uhlig, Annemarie; Bergmann, Lothar; Bögemann, Martin; Fischer, Thomas; Goebell, Peter; Leitsmann, Marianne; Reichert, Mathias; Rink, Michael; Schlack, Katrin; Trojan, Lutz; Uhlig, Johannes; Woike, Michael; et al. (Urologia Internationalis, 2024)
Introduction: We evaluated the effectiveness and safety profile of the tyrosine kinase inhibitor sunitinib in patients with advanced or metastatic renal cell carcinoma (a/mRCC) in a real-world setting. Methods: We analyzed data of adult a/ mRCC patients treated with sunitinib. Data were derived from the German non-interventional post-Approval multicenter STAR-TOR registry (NCT00700258). Progression-free survival (PFS), overall survival (OS), and adverse events (AEs) were evaluated using descriptive statistics and survival analyses for the entire cohort and patient subgroups. Results: A total of 116 study sites recruited 702 patients treated with sunitinib (73.1% male; median age 68.0 years; median Karnofsky index 90%) between November 2010 and May 2020. The most frequent histological subtype was clear cell RCC (81.6%). Sunitinib was administered as first-line treatment in 83.5%, as second line in 11.7%, and as third line or beyond in 4.8% of the patients. Drug-related AEs and serious AEs were reported in 66.3% and 13.9% of the patients, respectively (most common AE: gastrointestinal disorders; 39.7% of all patients). Conclusions: This study adds further real-world evidence of the persisting relevance of sunitinib for patients with a/mRCC who cannot receive or tolerate immune checkpoint inhibitors. The study population includes a high proportion of patients with unfavorable MSKCC poor-risk score, but shows still good PFS and OS results, while the drug demonstrates a favorable safety profile. The STAR-TOR registry is also registered in the database of US library of medicine (NCT00700258).
CRIS-Team Scopus Importer:2024-06-07
Keywords: Clinical routine; Renal cell carcinoma; Subgroup analyses; Sunitinib; Survival